Technical and Energy Performance of an Advanced, Aqueous Ammonia-Based CO2 Capture Technology for a 500 MW Coal-Fired Power Station - Li, K.; Yu, H.; Feron, P.; Tade, Moses; Wardhaugh, L. (American Chemical Society, 2015)
Using a rate-based model, we assessed the technical feasibility and energy performance of an advanced aqueous-ammonia-based postcombustion capture process integrated with a coal-fired power station. The capture process consists of three identical process trains in parallel, each containing a CO2 capture unit, an NH3 recycling unit, a water separation unit, and a CO2 compressor. A sensitivity study of important parameters, such as NH3 concentration, lean CO2 loading, and stripper pressure, was performed to minimize the energy consumption involved in the CO2 capture process. Process modifications of the rich-split process and the interheating process were investigated to further reduce the solvent regeneration energy. The integrated capture system was then evaluated in terms of the mass balance and the energy consumption of each unit. The results show that our advanced ammonia process is technically feasible and energy-competitive, with a low net power-plant efficiency penalty of 7.7%.